Vegetarianism: advantages and drawbacks in patients with chronic kidney diseases - Chauveau, Philippe; Combe, Christian; Fouque, Denis; Aparicio, Michel (Journal of renal nutrition, 2013)
Vegetarian diet is a very old practice that is liable to confer some health benefits. Recent studies have demonstrated that modification of the dietary pattern with a reduction of animal protein intake and increased consumption of plant-based foods could influence cardiovascular risk profile and mortality rate. Moreover, phosphate bioavailability from plant proteins is reduced. These statements could lead to some benefits for chronic kidney disease (CKD) patients. This review summarizes the characteristics and benefits of vegetarian diets in the general population and the potential beneficial effects of such a diet on phosphate balance, insulin sensitivity, and the control of metabolic acidosis in CKD patients. Potential drawbacks exist when a vegetarian diet is associated with protein intake that is too restrictive and/or insufficient energy intake, justifying an early and regular nutritional follow-up jointly assumed by a nephrologist and a renal dietitian.